EVALUASI KEBIJAKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 5 TAHUN 2002 - Roza, Aldi; Harahap, Tuti Khairani; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2019)
Policy Evaluation of Pekanbaru City Regulation Number 5 of 2002. This study aimsto determine Regional Regulation Number 5 of 2002 concerning Public Order in the City ofPekanbaru. This study uses a qualitative approach, with descriptive methods. Sources of data wereobtained from primary data sources, through direct observation and interviews with keyinformants, namely Pekanbaru City DPRD Members, Governmental Assistant I, Head ofPekanbaru City Satpol PP, Secretary of the Market Service, Chair of the Pekanbaru City MarketTraders Association, Chairperson of the Morning Market Traders Association Arengka, PKL inthe Kodim Market, PKL in Arengka Market and Community Representatives. Data analysistechniques used the tringulation method by comparing the results of interviews with thegovernment and street vendors in the field. The results of the study show that the Pekanbaru CityRegulation Regulation Number 5 of 2002 concerning Public Order Policy has not been fullyunderstood and adhered to by street vendors.